2020
DOI: 10.1101/2020.10.21.20216960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergency Response for Evaluating SARS-CoV-2 Immune Status, Seroprevalence and Convalescent Plasma in Argentina

Abstract: We report the emergency development and application of a robust serologic test to evaluate acute and convalescent antibody responses to SARS-CoV-2 in Argentina. The assays, COVIDAR IgG and IgM, which were produced and provided for free to health authorities, private and public health institutions and nursing homes, use a combination of a trimer stabilized spike protein and the receptor binding domain (RBD) in a single enzyme-linked immunosorbent assay (ELISA) plate. Over half million tests have already been di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…Therefore, in order to resolve this shortage and support state-led diagnostic efforts, many research laboratories have repurposed their expertise, skilled labor and equipment by developing and assembling in-house testing kits, among other efforts [4][5][6][7] . SARS-CoV-2 serological tests employ enzyme-linked immunosorbent assay (ELISA) 8,9 , immunofluorescence 10 and lateral flow techniques to detect antibodies directed against the nucleocapsid (N) and/or Spike (S) proteins of the viral proteome 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to resolve this shortage and support state-led diagnostic efforts, many research laboratories have repurposed their expertise, skilled labor and equipment by developing and assembling in-house testing kits, among other efforts [4][5][6][7] . SARS-CoV-2 serological tests employ enzyme-linked immunosorbent assay (ELISA) 8,9 , immunofluorescence 10 and lateral flow techniques to detect antibodies directed against the nucleocapsid (N) and/or Spike (S) proteins of the viral proteome 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In a breakthrough report, Ibarrondo et al described that SARS-CoV-2 IgG antibodies decayed early and rapidly after symptom onset in persons with mild disease [14]. Other studies confirmed that indeed there is a decay in IgG levels but at a slower rate and at later times than that reported by Ibarrondo et al [11, 15-21]. Although our understanding in the antibody dynamics is still incomplete, specific IgG levels appear to be maintained during 4-5 months, or even longer, if we consider our data from plasma non-donors, presented in figure 5A.…”
Section: Resultsmentioning
confidence: 95%
“…This kit was developed by Argentinean researchers from CONICET, Fundación Instituto Leloir and UNSAM together with Laboratorio Lemos S.R.L. The validation process determined that sensitivity to detect specific IgG raises to 90% after 3 weeks of symptoms onset while specificity is 100% [11]. Briefly, samples were loaded in wells pre-coated with recombinant SARS-CoV-2 Spike protein and RBD.…”
Section: Methodsmentioning
confidence: 99%
“…Performance characteristics of the kit indicate a sensitivity of more than 90% after 21 days and more than 95% after 45 days of symptoms onset. The specificity was set to be 100% (8). None of the funding sources provided economical support for the data collection, statistical analysis, or were used to write the manuscript, or to submit it for publication.…”
Section: Population and Settingsmentioning
confidence: 99%
“…Most of the neutralizing antibodies are directed against the S protein and more specifically to the receptor binding domain RBD (7). Multiple studies have shown that the majority of SARS-CoV-2-infected individuals produce S-and RBD-specific antibodies during the first 2 weeks of the primary response (8). In addition, monoclonal antibodies against this viral protein neutralize the virus in vitro and in vivo (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%